Applying the Operational Risk Management Approach to Improve Ground Operations Safety at King Fahd International Airport: A Field Study (The International Journal for Scientific Research, 2026)
This study aims to evaluate the effectiveness of implementing an operational risk management (ERM) approach in improving ground operations safety at King Fahd International Airport. The study employed a descriptive-analytical methodology, collecting field data through questionnaires and direct observations of ground operations personnel. The sample comprised 266 participants representing various job categories at the airport, providing a comprehensive view of the risk levels and preventive measures in place. The results showed a significant decrease in minor operational incidents and an improvement in employee awareness of risks and safety procedures. The study also highlighted the role of technology and continuous training in enhancing response capabilities and mitigating risks. Based on these findings, the study recommends further developing operational risk management programs, enhancing ongoing employee training, and integrating technological solutions for monitoring ground operations. It also emphasizes the importance of fostering a strong corporate safety culture to ensure the sustainability of these results.
Keywords: Operational Risk Management; Ground Operations Safety; King Fahd International Airport; Training and Safety; Risk Monitoring; Safety Culture; Operational Performance Improvement